Parents transmit happiness along with associated values and behaviors to their children: A lifelong happiness dividend? - Bruce Headey; Ruud J. A. Muffels; Gert G. Wagner (Institute for the Study of Labor (IZA), 2012)
There are strong two-way links between parent and child happiness (life satisfaction), even for 'children' who have grown up, moved to their own home and partnered themselves. German panel evidence shows that transmission of (un)happiness from parents to children is partly due to transmission of values and behaviors known to be associated with happiness (Headey, Wagner and Muffels, 2010, 2012). These values and behaviors include giving priority to pro-social and family values, rather than material values, maintaining a preferred balance between work and leisure, active social and community participation, and regular exercise. Both parents have about equal influence on the values and behaviors which children adopt. However, the life satisfaction of adult 'children' continues to be directly influenced by the life satisfaction of their mothers, with the influence of fathers being only indirect, via transmission of values and behaviors. There appears to be a lifelong happiness dividend (or unhappiness dividend) due to parenting. Structural equation models with two-way causation indicate that the life satisfaction of offspring can significantly affect the satisfaction of their parents, as well as vice-versa, long after the 'children' have left home. Data come from 25 waves of the German Socio-Economic Panel Survey (SOEP, 1984-2008). SOEP is the only panel survey worldwide in which data on life satisfaction have been obtained from parents and an adequate sub-sample of children no longer living in the parental home.
Keywords: D60; I31; J13; J22; C33; 330; life satisfaction; subjective well-being; child happiness; inter-generational transmission; German Socio-Economic Panel (SOEP); structural equation models; Zufriedenheit; Familiensoziologie; Generationenbeziehungen; Schätzung; Deutschland